南極湖沼調査に資する小型水中無人探査機（ROV）の開発 - 後藤, 慎平; ゴトウ, シンペイ; 山崎, 晋; ヤマザキ, ススム; 大村, 竜義; オオムラ, タツヨシ; 牛山, 和人; ウシヤマ, カズト; 脇嶋, 智晴; ワキシマ, トモハル; 井手, 一充; イデ, カズミツ; et al. (国立極地研究所, 2020)
南極大陸の露岩域に点在する湖沼では，南極独自の生態系の存在が近年の研究で明らかになってきた．宗谷海岸露岩域スカルブスネスの長池，仏池，くわい池では，コケ類・藻類・シアノバクテリアを主体とする円錐状の生物群集構造物が湖底に確認されている．一方で，この構造物の定量的な分布情報は得られておらず，調査手法も確立されていない．従来，これら湖底生物群集の観察・調査は，人が直接潜水することによって行われてきた．しかし，低温環境かつ隔離環境での潜水調査には時間的な制約が大きいうえに，人員・物資等の輸送が大規模なオペレーションになる．そのため，様々な湖沼で湖底生物群集の分布を広範囲に効率的に調査することが難しく，研究の進展を律速する大きな要因の一つとなっている．そこで本研究では，湖底生物群集の分布を定量化するため，南極湖沼の水中を調査することが可能な小型無人探査機（ROV）を新たに開発し，第58次および第59 次日本南極地域観測隊で試験的調査・運用を行った． In the recent study, unique ecosystemic existence became clear in the lakes around the Syowa Station. On the lake bottom of Naga, Hotoke, and Kuwai Lakes in Skarvsnes on the Sôya Coast, a cone-shaped biological community structure mainly consisting of mosses, algae and cyanobacteria have been confirmed. On the other hand, the process leading to fixation and growth from the invasion of the creature has not been eluci- dated. Conventionally, these lake surveys have been carried out by scuba diving. However, an extensive, effective investigation is difficult because time limitation is rigid for a diving investigation in the low-temperature environment. Therefore, it is difficult to investigate the distribution of lake bottom communities widely and efficiently in various lakes, and it is one of the major factors that limit the progress of research. In this study, we aimed to create visual information as “Habitat mapping” from the lake surface and underwater by developing a new ROV, which is usable at the Antarctic lake surveys during the 58th and 59th Japanese Antarctic Research Expeditions. departmental bulletin paper